DIAGNOSTIC AND METHODOLOGICAL COMPLEX FOR ASSESSING THE DEGREE OF FORMATION OF THE COMMUNICATIVE UNIVERSAL EDUCATIONAL ACTION «ASKING QUESTIONS» - Alekseeva, Tatiana; Sergeeva, Larisa; Kamenskih, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article deals with the actual problem of effective pedagogical management of the process of formation of communicative universal educational action «asking questions» in junior schoolchildren.In order to solve the problem under study, this paper presents a diagnostic and methodological complex for assessing the degree of formation of the designated universal educational action in elementary school students, which includes a system of criteria, scaled nominative indicators, a theoretical model of the formation of the designated universal educational action in students, consisting of five possible levels - standards, as well as diagnostic tools adapted to the age characteristics of younger schoolchildren.The empirical experience of using diagnostic tools in the practice of an elementary school teacher, qualitative and quantitative analysis of the results of the study made it possible to obtain data on the degree of formation of the components of the communicative universal educational action «asking questions» in the educational activities of elementary school in junior schoolchildren.